2023
DOI: 10.1002/aisy.202200404
|View full text |Cite
|
Sign up to set email alerts
|

Toward Robotic Sensing and Swimming in Granular Environments using Underactuated Appendages

Shivam Chopra,
Drago Vasile,
Saurabh Jadhav
et al.

Abstract: Granular environments, such as sand, are one of the most challenging substrates for robots to move within due to large depth‐dependent forces, unpredictable fluid/solid resistance forces, and limited sensing capabilities. An untethered robot is presented, inspired by biological diggers like sea turtles, which utilize underactuated appendages to enable propulsion and obstacle sensing in granular environments. To guide the robot's design, experiments are conducted on test appendages to identify the morphological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Particulate matter is widely present in both the natural environment and engineering applications [1,2]. The ability to undergo body-deformation that generate appropriate reaction forces from the granular medium is critical for the survival of most organisms and constitutes a vital skill for robots employed in various fields, including rescue [3,4], the underground exploration [4][5][6], and the control of rheological responses [7][8][9]. These organisms or structures can be regarded as being composed of fundamental units akin to simply supported beams in the field of mechanics [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Particulate matter is widely present in both the natural environment and engineering applications [1,2]. The ability to undergo body-deformation that generate appropriate reaction forces from the granular medium is critical for the survival of most organisms and constitutes a vital skill for robots employed in various fields, including rescue [3,4], the underground exploration [4][5][6], and the control of rheological responses [7][8][9]. These organisms or structures can be regarded as being composed of fundamental units akin to simply supported beams in the field of mechanics [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…These various types of movements have inspired the development of robotic systems, including robotic snakes ( Marvi et al, 2014 ) with sidewinding and flipper-driven ( Mazouchova et al, 2013 ) walking on the surface of the granular media. Underneath the surface of granular media, self-burrowing of a mole crab-inspired robot with legs ( Treers et al, 2022 ), burrowing with underactuated appendages resulting in an asymmetric profile between power and return strokes ( Chopra et al, 2023 ), and growing with a root-like robot ( Naclerio et al, 2021 ) all show successful burrowing. More reviews on bioinspired robotic burrowers can be found in ( Wei et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The major challenge to horizontal burrowing motion is the small difference between resistive forces in opposite directions. We do not include the works such as ( Chopra et al, 2023 ) or ( Li et al, 2021 ) in this comparison because they use articulated fins and not linear actuation with passively deployed fins, however we note that they reach 45% and 9% translation ratios, respectively. This is an important distinction because stroke length and appendage size are inherently coupled when burrowing is achieved through direct appendage actuation.…”
Section: Introductionmentioning
confidence: 99%